Identification of autoantibodies expressed in acquired aplastic anaemia. (1st November 2012) - Goto, Maki; Kuribayashi, Kageaki; Takahashi, Yusuke; Kondoh, Takashi; Tanaka, Maki; Kobayashi, Daisuke; Watanabe, Naoki
Summary Acquired aplastic anaemia (aAA) is recognized as an autoimmune disorder; however, the autoantigens and target cells involved remain elusive. Expression of autoantibodies and their target cells were examined using the haematopoietic cell line K562 and bone marrow stromal cell line hTS‐5; 43·5% and 21·7% of aAA expressed autoantibody against K562 and hTS‐5 cells, respectively. The autoantigens were identified by serological identification of antigens through recombinant cDNA expression cloning. This study indicates that haematopoietic cells are the targets of immune abnormality in aAA. These autoantibodies may be utilized to distinguish patients associated with immune abnormality from bone marrow failure syndrome.